MATTER OF DEATH AND LIFE. - YALOM, IRVIN. YALOM, MARILYN (PIATKUS BOOKS, 2021)
Internationally renowned psychiatrist and author Irvin Yalom has devoted his career to counselling those suffering from anxiety and grief. But never had he faced the need to counsel himself until his wife, esteemed feminist author Marilyn Yalom, was diagnosed with cancer. In this book, Marilyn and Irvin share how they took on profound new struggles: Marilyn to die a good death, Irvin to live on without her. In alternating accounts of their last months together and Irvin's first months alone, they offer us a rare window into coping with death and the loss of one's beloved.